ELECTRONIC DOCUMENT MANAGEMENT SYSTEM AS A TOOL FOR THE DIGITALIZATION OF ACCOUNTING PROCESSES IN DOMESTIC ENTERPRISES - LOPATOVSKYI, Viktor; BOHATCHYK, Liudmyla; POMARANSKA, Oksana; LOPATOVSKA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
It was determined that in the conditions of rapid development of information and digital technologies, along with the paper form of document flow, electronic documentation of the processes of collection, processing, systematization and transmission of accounting information is actively spreading at domestic enterprises. A study of the essence of electronic document flow was conducted, the main principles of its construction and key efficiency criteria were established. The main regulatory and legal documents that regulate the organizational and legal foundations of electronic document flow were analyzed. It was proven that the use of electronic documents allows to significantly speed up the processing of information in various areas of accounting work, and helps business entities improve the quality of communicative interaction with counterparties and regulatory authorities. It was established that when making a decision on the use of electronic documents in the document flow system of a business entity, persons responsible for the organization and maintenance of accounting must clearly identify those areas of accounting work that will be transferred to electronic format, as well as determine the methods of their interaction with other forms of documentation. An algorithm for implementing an electronic document management system at domestic enterprises is proposed, which provides for: fixing the procedure for maintaining electronic document management in the organizational documents of the enterprise; choosing an electronic document management system; training accounting staff to work with the selected electronic document management system; notifying partners about the transition to an electronic documentation system.